Projects as instrumentalization devices of public policies in the field - Berger, Matías; Marcos, María Florencia (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
In this article, we present an ethnographic analysis of the formulation process of a project produced to get access at financial resources provides by public policies of rural development of Argentina for an horticultural farmers association in Buenos Aires suburban area. The project constitutes a device that uses techniques and procedures and through which the program is instrumentalized in the field, framing problems and demands in the logic and language of bureaucratic field. To carry out our analysis, we describe the participation of organized horticultural producers, state agents and academics and the interpretations elaborated by them from multiple interlocking structures of significance that allow us to understand the perspectives and approaches involved in design and implementation of state policies.